DEVELOPMENT INVENTORI SYSTEM METODE TREND MOMENT UNTUK OPTIMALISASI BERBASIS RFID - Muhamad Sidik; Reni Veliyanti (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
In the warehouse department or warehouse in companies including PT. Semarang Packing Indonesia has a service system that still has not maximized the current technological developments that are growing rapidly. Included in the warehouse inventory system which often occurs is not available stock and excessive stock. This causes the inventory function in the warehouse not to work optimally. From these problems,. This system includes controlling inventory in the warehouse for purchases so as to reduce excessive or insufficient stock so that the stockter inventory is controlled, as well as the data input process that utilizes RFID so as to speed up the time in the data input process. This system uses the PHP and MYSQL programming languages as the database and utilizes the PHP Framework, namely CodeIgniter, in making this website. With a web-based system, it makes it easier for employees to process data in a timely manner.